Recreational sports participation: Malaysians' motives for participation in recreational sports / Kwame Ampofo-Boateng - Kwame Ampofo-Boateng, . (2010)
Background. One of the most important issues confronting sports psychologists is the motive people assign for participating in sports (Ampofo-Boateng, 2009b; Duda, 1989). The present research continued this trend by investigating the motives Malaysians' assign for participation in recreational sports. Aims. The aims of the current research were two-fold: (a) to examine the motives Malaysians assign for taking part in recreational sports; and (b) to investigate the influence of demographic variables on the motives Malaysians' provide for participation. Method. A modified version of Duda's (1989) Purpose of Sport Questionnaire was used as the research instrument, and was administered to 602 randomly selected Malaysians (resident in the Selangor State of Malaysia). Results. The data collected was collated and statistically analysed using SPSS. Principal component analysis of the data revealed 6 motives for taking part in recreational sport. They were: (a) competitiveness and social status; (b) physically active lifestyle; (c) self-esteem; (d) good citizens; (e) high status careers; and (f) teaching tools. Overall, the results also showed the influence of demographic variables of occupation, income and race on motives for taking part in recreational sports. Conclusion. The implications of the findings as they relate to the devising of strategies to encourage Malaysians to participate in recreational sports are discussed, and suggestions offered for future research.